The testament of Mary - Tóibín, Colm, 1955- (Scribner, 2012)
A provocative imagining of the later years of the mother of Jesus finds her living a solitary existence in Ephesus years after her son's crucifixion and struggling with guilt, anger, and feelings that her son is not the son of God and that His sacrifice was not for a worthy cause.